Book Review: Thomas Murray on Doping – Are We Doing the Right Thing? - Stoffel, Bertrand Alexandre (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2019)
Anti-doping policy is one of the most important international sport policies. Yet its justification remains controversial. Good Sport: Why Our Games Matter – and How Doping Undermines Them, Oxford University Press 2018, by Thomas Murray (President Emeritus of the Hastings Center) provides a convincing and comprehensive exploration of ethical questions raised by biomedical enhancements in sport.